Viability and Vigor Test of Local Rice Seeds in Kuantan Singingi - Marlina, Gusti; Syarif, Auzar; Gustian; Yusniwati (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2024)
Seeds are a valuable plant material for agriculture. The Kuantan Singingi district has many local rice seeds that can be developed, but these have not yet passed standard testing. This study aimed to determine the physical and physiological qualities of the seeds of two local rice genotypes in Kuantan Singingi Regency. This research was conducted in a completely randomized design (CRD), which was repeated four times. The factor tested consisted of two rice genotypes: the white and yellow genotypes. เว็บสล็อต | R4shub The parameters observed were the percentage of the First Count Test (FCT) of germination capacity (GP), Maximum Growth Potential (MGP), Root and Shoot Growth Test (RSGT), and Seedling Growth Rate Test (SGRT). The collected data were analyzed by ANOVA at the 5% level and further tested by the LSD test. The results showed that FCT (%), GP (%), and Vigor (%) provide high figures according to SNI. Meanwhile, the IVT of all seeds on day 2 germinated. Based on the data from the RSGT and SGRT, all seed growth was normal. Keywords: Kuantan Singingi, local seeds, viability, vigor